Methods of Bank Valuation in the Age of Globalization - A. Karminsky; E. Frolova (Vestnik MGIMO-Universiteta)
This paper reviews the theory ofvalue-based management at the commercial bank and the main valuation methods in the age of globalization. The paper identifies five main factors that significantly influence valuation models selection and building: funding, liquidity, risks, exogenous factors and the capital cushion. It is shown that valuation models can be classified depending on underlying cash flows. Particular attention is paid to models based on potentially available cash flows (Discounted cash flow-oriented approaches, DCF) and models based on residual income flows (Residual income-oriented approaches). In addition, we consider an alternative approach based on comparison with same sector banks (based on multiples). For bank valuation equity discounted сash flow method is recommended (Equity DCF). Equity DCF values equity value of a bank directly by discounting cash flows to equity at the cost of equity (Capital Asset Pricing Model, CAPM), rather than at the weighted average cost of capital (WACC). For the purposes of operational management residual income-oriented approaches are recommended for use, because they are better aligned with the process of internal planning and forecasting in banks. For strategic management residual income-oriented methods most useful when expected cash flows are negative throughout the forecast period. Discounted сash flow-oriented approaches are preferable when expected cash flows have positive values and needs for models using is motivated by supporting the investment decisions. Proposed classification can be developed in interests of bank management tasks in the midterm in the age of globalization.